Evaluación de la incorporación de la fruta Passiflora Edulis (maracuyá) en el proceso de producción de cerveza artesanal tipo pale ale (2019)
This project describes the activities carried out in order to select a fruit to be incorporated into the Pale Ale craft beer production process, giving an extra value, maintaining BJCP’s parameters according to American Pale style; coming up with passion fruit (Passiflora edulis f. flavicarpa) as the more appropriate thus its organoleptic properties and high demand in Colombia. After this, it was concluded to add the fruit into the fermentation stage in order to avoid volatile compound and sensorial losses. This is how three craft beers were developed seeking to find one whose flavor and smell is balanced between the bitterness of the hops and the fruity note of the passion fruit. To achieve this, three concentrations were evaluated (0.20, 0.14, and 0.06 kg passion fruit per liter of beer), starting with the extraction of the pulp, its subsequent pasteurization and finally extraction of the juice, as substance added to the process. The beers produced were analyzed microbiologically to ensure their compliance with a drink suitable for human consumption, obtaining positive results in each of the tests. The best formulation was selected through the results obtained in a survey of preference evaluating its color, smell, taste, and mouthfeel, made by a brewmaster and common people. It is concluded that the craft beer with passion fruit could be placed on the market, since the passion fruit turned out to be a useful adjunct to make a difference compared to the beers commercialized normally.